Treatment Patterns of EGFR-Mutation Positive Non-Small Cell Lung Cancer Patients in East Asia and Western Europe: Results from an Online Survey - Ettore, Mari; Carmen, Escorial; Armen, Andreasyan; Aimé, Giorlando María; Carolina, Gabay; Elias, Ortega; Laura, Schnetter; Luis, Mendoza (British Journal of Healthcare and Medical Research, 2023)
Background: The Epidermal Growth Factor Receptor (EGFR) mutations and the EGFR-Tyrosine Kinase Inhibitors (TKIs) have generated a major paradigm shift in the management of Non-Small-Cell-Lung-Cancer (NSCLC). EGFR-mutated NSCLC is a genetically heterogeneous disease with significant variability in the prevalence of EGFR mutation being more common in females than in males and in East Asian than in Caucasian patients. Objectives and Methods: This cross-sectional survey conducted by web-based physician auto-completion forms using an IQVIA platform for data collection on NSCLC patients through the same questionnaire in 8 countries in East Asia and Western Europe aimed to describe the patterns of clinical NSCLC care. Results: Similar proportion of EGFR mutation testing was reported in East Asia and Western Europe, with higher prevalence of EGFR mutation in East Asia than Western Europe as expected. The EGFR Exon 19 deletions are more frequent in East Asia than in Western Europe, and vice versa for the EGFR Exon 21 L858R mutation. Treatment of patients with metastatic NSCLC varies in both Regions. The use of Immune Checkpoint Inhibitors (ICIs) in first, second and third line is more frequent in Western Europe than in East Asia while the use of EGFR-TKI is more frequent in East Asia in all 3 lines. Chemotherapy is used less in the first and second line in Western Europe, but its third line use is higher than in East Asia. All metastatic NSCLC EGFR mutation positive patients received first-line EGFR-TKIs in both Regions. However, the use of ICIs was higher in second and third line in Western Europe. Conclusions: This research highlights the differences in the current standard of care of metastatic and EGFR mutation positive metastatic NSCLC patients in two key world regions.